E.M. Forster's Modernism - Medalie, David. author. aut Link
IX, 213 p.
Keywords: This volume is a comprehensive investigation into Forster's relationship to Modernism. It advances the argument that Forster's fiction embodies an important strand within modernism and in doing so makes the case for a new definition and interpretation of "modernism".